2019
DOI: 10.1007/s00431-019-03445-1
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory survey on the state of training in adolescent medicine and health in 36 European countries

Abstract: The development of adolescent health and medicine as a medical discipline lags behind in Europe compared with other regions of the world. This study aims to evaluate the structure and content of adolescent medicine and health training curricula for medical students, paediatricians, and other primary care physicians in the European region. A questionnaire survey was sent by e-mail to experts in the field from 36 European countries, addressing the content of adolescent health issues. Data was obtained from all 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Third, only eight experts reported that their countries' schools were equipped to respond to mental health crises, while schools are places where adolescents spend a large part of their time and where the possibilities of early detection of mental health and early response to is real. 32,33 Fourth, our survey shows that only half of the countries have policies that promote the training of PCPs in the area of adolescent mental health, a situation confirmed by recent MOCHA publication; 34 this situation could be improved in introducing a few specific training objectives in the training curricula of PCPs and students. 35…”
Section: Discussionmentioning
confidence: 63%
“…Third, only eight experts reported that their countries' schools were equipped to respond to mental health crises, while schools are places where adolescents spend a large part of their time and where the possibilities of early detection of mental health and early response to is real. 32,33 Fourth, our survey shows that only half of the countries have policies that promote the training of PCPs in the area of adolescent mental health, a situation confirmed by recent MOCHA publication; 34 this situation could be improved in introducing a few specific training objectives in the training curricula of PCPs and students. 35…”
Section: Discussionmentioning
confidence: 63%
“…The unmet training needs of healthcare professional in adolescent medicine is a global as well as a regional challenge [ 25 27 ]. Adolescents make up more than 25% of the population of Gulf Cooperation Council (GCC) countries, a percentage that is far higher than that in other high-income countries, yet their health status and health care needs are not given proportional attention in the region [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that females tend to demonstrate higher transition readiness as they tend to mature earlier [ 21 ]. Other studies demonstrated positive associations for transition readiness in higher median household income [ 25 ], while parent education and household size has not shown to have significant association with transition readiness [ 24 ]. On the other hand, some of the advantages of this study is the use of a provider administered questionnaire, as opposed to a self-administered questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries the training of pediatricians in the area of mental health and adolescent health is far from optimal, ( 58 ), which is unfortunate given the physician's stress initiated by self-harm and suicidal behavior ( 59 ). This article thus provides some clues on how practitioners can address, as first-line professionals, such situations.…”
Section: Conclusion: a Role To Play For Pediatriciansmentioning
confidence: 99%